فعالية استخدام الإستراتيجية مطابقة بطاقة الرقم القياسي Index Card Match في ترقية مهارة القراءة لطلاب الصف السابع بالمدرسة المتوسطةالحكومية العاشرة سليمان - Fauziah, Rihanatul; Nurhadi, Nurhadi (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
This research is motivated by the low reading comprehension of Arabic which is possessed by students of Middle School 10 Sleman in understanding reading texts because of the absence of a linguistic environment and active, so it caused a lack of interest and motivation for learning in the learning process. This study aims to improve reading skills in Arabic for 7th grade students of Middle School 10 Sleman especially in understanding reading texts by using the Index Card Match strategy in learning reading skills. With this research, it is expected to be able to help teachers in the learning process of reading Arabic skills and improve students' ability to read. In its implementation, this study used a quasi-quantitative approach with the Experimental method. To find out the extent of the effectiveness of the Index Card Match strategy in learning Arabic reading skills, the formula used is the t-test. This study resulted in differences in statistical calculations in mean values ??in the experimental group and the control group. For the experimental group reached an average of 81.28 and the control group 76.88. The value of "t" counts 2.335 and "t" table 2.042 so that "t" counts greater than "t" table, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected and there are significant differences. From the results above the researchers concluded that the use of the Index Card Match strategy in learning Arabic reading skills was effective so that it could improve reading skills in 7th grade students of Middle School 10 Sleman.